Visual Securitization: Commemorating the Partisan War in Lithuanian Foreign and Security Policy - Rimaitė-Beržiūnienė, Viktorija (Politologija, 2022)
In 2008 and 2014 the Russian-Georgian war, the military conflict in Ukraine, and the annexation of Crimea have had an impact on Lithuanian foreign and security policy. In the context of these events, Lithuania was concerned about the mobilization of conventional security measures, i.e., strengthening its national defense sector. However, the role as well as the impact of “soft” (unconventional) response devices and strategies in the Lithuanian case has still received little academic interest. This paper, using the analysis of visual collective memory practices (monuments), aims to show the links between collective memory as well as its visually tangible forms and the formation of foreign and security policy in Lithuania. By examining the visual practices reminiscent of guerrilla warfare built in Lithuanian public spaces after 2014, it is revealed how the use of collective memory contributed to the perceived threat from Russia, which had a significant impact on the formation and implementation of foreign and security policy.